2012
DOI: 10.3109/02770903.2012.663847
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Network System for Providing Proper Inhalation Technique by Community Pharmacists

Abstract: Our network system may improve asthma control and adherence to inhalation regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…This cut-off score enabled us to identify patients who were non-adherent to inhaled medicine and resulted in a reliable AUC. Fiftytwo (46%) of 114 patients with asthma were accordingly classified as non-adherent, which is similar to the rate reported in our previous study (24,29). Age is associated with adherence to asthma inhalation treatment, with some studies revealing younger patients to be more non-adherent than older adults (29)(30)(31).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This cut-off score enabled us to identify patients who were non-adherent to inhaled medicine and resulted in a reliable AUC. Fiftytwo (46%) of 114 patients with asthma were accordingly classified as non-adherent, which is similar to the rate reported in our previous study (24,29). Age is associated with adherence to asthma inhalation treatment, with some studies revealing younger patients to be more non-adherent than older adults (29)(30)(31).…”
Section: Discussionsupporting
confidence: 71%
“…The ASK-12 questionnaire was administered as described elsewhere in the literature (24 Asthma Control Test (ACT) (26) was also implemented on the same day. The cut-off value of the ASK-12 total score used to identify non-adherence to inhalation therapy was determined using pharmacy-refill data as an objective measurement.…”
Section: Study Protocolmentioning
confidence: 99%
“…It has been shown that pharmaceutical care of patients with obstructive respiratory diseases improves medication adherence [24][25][26][27] and achieves a better use of inhalers [26,[28][29][30] and control of the disease [31,32]. In a randomized controlled study to investigate the effect of a simple educational intervention concerning DPI technique delivered by community pharmacists to patients with asthma, a simple educational intervention taking only 2.5 min and targeting inhaler technique was feasible for delivery by community pharmacists and resulted in improved clinical and humanistic outcomes for patients with asthma [33].…”
Section: Discussionmentioning
confidence: 99%
“…Other health professionals, such as physicians in other areas of specialty, respiratory therapists, nurses or pharmacists may even be involved in the education process for patients. [24][25][26] Future work should focus on the effectiveness of the review at each visit and on the knowledge and training of health professionals in this field.…”
Section: Discussionmentioning
confidence: 99%